An evaluation of measured indoor conditions and student performance using d2 Test of Attention. (15th April 2022) - Woo, Jin; Rajagopalan, Priyadarsini; Andamon, Mary Myla
Abstract: This study aims to investigate if a relationship can be established between measured indoor conditions and student performance in classroom settings. Ten classrooms in five Victorian schools in Australia were selected to monitor indoor conditions and measure student attention and concentration performance using a neuropsychological assessment, d2 Test of Attention. Correlation analysis revealed that the student performance parameters, particularly TN (reaction time, speed) and CP (accuracy), established a low to moderate correlation with most of the indoor condition parameters except CO2 concentration level. An exploratory stepwise multiple regression analysis identified that the common predictors of TN are relative humidity (RH), mean radiant temperature (MRT) and PM2.5 and the common predictors of CP are MRT and PM2.5 . Interestingly, relative humidity (RH) and CO2 concentration level are the important predictors of both TN and CP among the seven environmental variables in the hierarchical multiple regression model when controlling the non-environmental variables such as student age and school terms. As thermal comfort related variables such as air temperature, air velocity and MRT were correlated with school terms due to seasonal changes, they contributed to the shared variance along with school terms in the regression model. Understanding the unique and shared contribution of the indoor condition parameters to student performance can help to develop strategies to improve school building performance. Highlights: Establishing the relationship between indoor conditions and student performance. Common predictors of TN (reaction time, speed) and CP (accuracy) are MRT and PM2.5 RH and CO2 are the important predictors when controlling age and school terms. Understanding the contribution of the indoor conditions to student performance.